(untitled) (International Journal of Engineering and Computer Science, 2017)
A delay tolerant network(DTN) is a collection of infrastructure-less nodes, with no communication medium. These nodes cooperate dynamically to meets certain immediate needs. Therefore, each node acts as a router also beside being merely a host. Security issues have thus become more challenging in these networks due to its dynamic nature. Thus these networks are vulnerable to different kinds of attacks because of which security has always been a major concern. This paper uses ferry-based [11] mechanism for providing security and maintaining consistency throughout the network.